On the possibility of detecting ultrashort period exoplanets with LISA. (10th November 2018) - Wong, Kaze W K; Berti, Emanuele; Gabella, William E; Holley-Bockelmann, Kelly
ABSTRACT: Cunha, Silva & Lima recently reexamined the possibility of detecting gravitational waves from exoplanets, claiming that three ultrashort period systems would be observable by LISA. We revisit their analysis and conclude that the currently known exoplanetary systems are unlikely to be detectable, even assuming a LISA observation time T obs  = 4 yr. Conclusive statements on the detectability of one of these systems, GP Com b, will require better knowledge of the system's properties, as well as more careful modelling of both LISA's response and theG alactic confusion noise. Still, the possibility of exoplanet detection with LISA is interesting enough to warrant further study, as gravitational waves could yield dynamical properties that are difficult to constrain with electromagnetic observations.